1997
DOI: 10.1099/0022-1317-78-6-1199
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of potato spindle tuber viroid by mutations in the left terminal loop.

Abstract: Infectivity studies with highly infectious RNA inocula generated by ribozyme cleavage were used to compare the biological properties of three apparently nonviable mutants of potato spindle tuber viroid (PSTVd). One of these mutants (PSTVd-P) contains three nucleotide substitutions in the left terminal loop, and mechanical inoculation of tomato seedlings with RNA transcripts at levels equivalent to 10 3 -10 5 times the ID 50 for PSTVd-Intermediate failed to result in systemic infection. Viable progeny containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 27 publications
(39 reference statements)
1
35
0
Order By: Relevance
“…This rod-like structural model is well supported by microscopic and biophysical studies (Riesner et al, 1979), chemical/enzymatic mapping , and nuclear magnetic resonance spectroscopic studies (left terminal domain; Dingley et al, 2003). Mutational studies support the importance of the rod-like secondary structure of PSTVd for infection (Hammond and Owens, 1987;Hammond, 1994;Wassenegger et al, 1994;Hu et al, 1997;Owens and Thompson, 2005). Biophysical/chemical studies identified several premelting regions of low thermostability in the native structure of PSTVd, and denaturation of this structure initiated at these regions and subsequent refolding led to the formation of metastable hairpin (HP) structures via pairing of distant complementary nucleotide sequences (Riesner, 1987;Riesner et al, 1979).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…This rod-like structural model is well supported by microscopic and biophysical studies (Riesner et al, 1979), chemical/enzymatic mapping , and nuclear magnetic resonance spectroscopic studies (left terminal domain; Dingley et al, 2003). Mutational studies support the importance of the rod-like secondary structure of PSTVd for infection (Hammond and Owens, 1987;Hammond, 1994;Wassenegger et al, 1994;Hu et al, 1997;Owens and Thompson, 2005). Biophysical/chemical studies identified several premelting regions of low thermostability in the native structure of PSTVd, and denaturation of this structure initiated at these regions and subsequent refolding led to the formation of metastable hairpin (HP) structures via pairing of distant complementary nucleotide sequences (Riesner, 1987;Riesner et al, 1979).…”
Section: Introductionmentioning
confidence: 62%
“…PSTVd replicates efficiently in cultured cell protoplasts and easily develops systemic infection in this plant (Hu et al, 1997;Zhu et al, 2001). Through this analysis, we identified multiple loops/bulges as functional motifs that are critical for replication or trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, P1/HC-Pro can enhance miRNA accumulation (16,24,55). To test the effects of these suppressors on srPSTVd accumulation, we used Nicotiana benthamiana for the following reasons: (i) PSTVd actively replicates in N. benthamiana plants (38,104) as well as in protoplasts of cultured cells (67), and (ii) RNA silencing protocols, including assays of viral suppressor functions, have been well established in N. benthamiana plants (72) and cultured cells (68). Therefore, N. benthamiana provides a convenient experimental system to study RNA silencing and PSTVd biology.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pRZ6-2 containing the cDNA of PSTVd Int (pRZ6-2-Int) was constructed by Hu et al (1997) and was a gift from Robert Owens. All PSTVd mutants described in this article were generated by site-directed mutagenesis based on this template, as previously described (Zhong et al, 2008).…”
Section: Methods Cdna Construction Of Pstvd Loop 6 Mutantsmentioning
confidence: 99%